2020
DOI: 10.1155/2020/4282316
|View full text |Cite
|
Sign up to set email alerts
|

Active Vision Therapy for Anisometropic Amblyopia in Children: A Systematic Review

Abstract: Purpose. The aim of the study was evaluation of the scientific evidence about the efficacy of vision therapy in children and teenagers with anisometropic amblyopia by performing a systematic literature review. Methods. A search was performed using 3 searching strategies in 4 different databases (PubMed, Web of Science, Scopus, and PruQuest). The quality of the included articles was evaluated using two tools for the risk of bias assessment, ROBINS-I for nonrandomized studies of intervention (NRSI), and ROB 2.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
(76 reference statements)
1
22
0
Order By: Relevance
“…Amblyopia research has experienced considerable progress in the last few decades, providing clinicians with more knowledge about the neural basis of the amblyopic visual system and new therapeutic approaches. However, there is a wide heterogeneity in the methodology of vision therapy treatment for amblyopia, according to the scientific literature [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amblyopia research has experienced considerable progress in the last few decades, providing clinicians with more knowledge about the neural basis of the amblyopic visual system and new therapeutic approaches. However, there is a wide heterogeneity in the methodology of vision therapy treatment for amblyopia, according to the scientific literature [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, vision therapy has been suggested to be an effective option to promote visual rehabilitation and even to accelerate recovery when combined with patching [ 8 ]. New trends in computer-based active vision therapy have been developed for amblyopia treatment, such as the use of perceptual learning environments [ 9 , 10 , 11 ], dichoptic stimulation [ 12 , 13 , 14 ] and binocular training [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of vision-based treatments for patients with amblyopia have been examined in systematic reviews comparing patching against atropine [29][30][31] or binocular treatments against patching. [32][33][34] Only one review 35 included a meta-analysis, which was limited to two studies and two treatments. In general, published systematic reviews and meta-analyses found no significant differences between the various vision-based amblyopia treatments.…”
Section: Key Messagesmentioning
confidence: 99%
“…But minus and plus lenses connected in flipper glasses have shown good effect as a training tool (Sterner, 2004). Hernández-Rodríguez & Piñero (2020) come to the conclusion that vision therapy looks promising for the treatment of amblyopia in children.…”
Section: Visual Acuity Reading Speed and Accommodationmentioning
confidence: 99%